The relationship between coach-created motivational climate and athletes' challenge and threat perceptions - Muharrem Aydın; İhsan Sarı (Nicolaus Copernicus University in Toruń, 2021)
The aim of this research was to examine the relationship between coach-created motivational climate and athletes' perception of challenge and threat states. For this purpose, 257 athletes from individual and team sports between the ages of 13-18 voluntarily participated in the research. Challenge and Threat in Sport (CAT-Sport) Scale, and Empowering and Disempowering Motivational Climate Questionnaire were used as the data collection tools. Descriptive statistics, Pearson correlation analysis and hierarchical regression analysis were conducted in SPSS 17. Pearson correlation analysis showed that challenge was positively and significantly correlated with empowering motivational climate along with its sub-dimensions. Also, threat positively and significantly correlated with disempowering motivational climate and its sub-dimensions. Regression analysis, after controlling for age, gender, sport type, sport experience, number of weekly training and weekly training hours, revealed that empowering motivational climate positively and significantly predicted challenge and disempowering motivational climate positively and significantly predicted threat. In the subscale level, task-involving and autonomy-supportive motivational climates positively and significantly predicted challenge and controlling motivational climate positively and significantly predicted threat. The findings emphasized the importance of the coach-created motivational climate for athletes challenge and threat in youth sports. The findings were discussed in line with the relevant literature and some suggestions for coaches were provided.